Urgensi Penerapan Mediasi Penal Dalam Sistem Peradilan Pidana Di Indonesia - Zondrafia Zondrafia; Kristiawanto Kristiawanto; Mohamad Ismed (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
Retributive justice-focused law enforcement against criminals can be ineffective. Convictions tend to be useless since victims' losses, damages, and injuries are overlooked. To overcome this, criminal case settlement led to restorative justice. Several law enforcement authorities, including the Police, Attorney General's Office, and Supreme Court, have adopted internal regulations on restorative justice-based penal mediation. Restorative justice settlements are currently limited to select circumstances, and the worth of losses that can be remedied through restorative justice mediation is limited. In Indonesia's criminal justice system, it's difficult to implement a restorative justice-based penal mediation method. No concrete criminal procedural statute binds law enforcement officers to bring cases to mediation, hence the restorative justice-based penal mediation method cannot be administered with legal certainty. Criminal procedural law is fundamental for enforcing substantive criminal law.Keywords: Mediation Penal; Criminal Justice System AbstrakPenegakan hukum yang berfokus pada keadilan retributif terhadap pelaku kejahatan dapat menjadi tidak efektif. Hukuman cenderung tidak berguna karena kerugian, kerusakan, dan cedera korban diabaikan. Untuk mengatasi hal tersebut, penyelesaian perkara pidana bermuara pada keadilan restoratif. Beberapa aparat penegak hukum, termasuk Kepolisian, Kejaksaan Agung, dan Mahkamah Agung, telah mengadopsi peraturan internal tentang mediasi penal berbasis keadilan restoratif. Penyelesaian keadilan restoratif saat ini terbatas pada keadaan tertentu, dan nilai kerugian yang dapat diperbaiki melalui mediasi keadilan restoratif terbatas. Dalam sistem peradilan pidana Indonesia, sulit untuk menerapkan metode mediasi penal berbasis keadilan restoratif. Tidak ada undang-undang acara pidana yang konkrit mengikat aparat penegak hukum untuk membawa kasus ke mediasi, sehingga metode mediasi penal berbasis keadilan restoratif tidak dapat dijalankan dengan kepastian hukum. Hukum acara pidana merupakan dasar untuk menegakkan hukum pidana substantif.Kata Kunci : Mediasi Penal, Sistem Peradilan Pidana